The Growth of Islamic Schools in Singkawang in the Colonial Era - Prabowo, Mohammad Rikaz; Firmansyah, Andang; Mirzachaerulsyah, Edwin (AT-TURATS, 2024)
The purpose of this study is to describe the development of Islamic schools in Singkawang during the Dutch East Indies colonial era (1901-1942). This era was marked by the transformation of Islamic education from traditional to formal, which was driven by the need to integrate general subjects. Interestingly, Islamic schools were able to exist amidst the rapid growth of Catholic Mission schools and the dominance of the Chinese community in Singkawang.Based on the results of the study through historical methods with the stages of heuristics, verification, interpretation, and historiography, it shows the following. Traditional Islamic education still dominated in the early 20th century through pengajian and alim-ulama as teachers. This practice occurred in several places around Singkawang, such as in the large mosque (Jami), surau in Selakau led by H. Muhammad As'ad, Semelagi, and other Malay villages. Driven by the development of Pan-Islamism, the existence of educated natives, and the wild school ordinance, traditional Islamic education was transformed into formal schools. Islamic schools that were once established in Singkawang during this era included the Islamiyah School in the city center, Madrasah in Semelagi Besar, Semelegi Kecil, Sungai Daun, Setapuk Besar, Madrasah Diniyah Setapuk, and Ahhadiah School Sedau. The curriculum used continued to emphasize Islamic religious studies plus general subjects in the three-year Volkschool and the five-year Standaarschool. The existence of Islamic schools in this city has encouraged the birth of the national movement with the establishment of various national movement organizations.Tujuan penelitian ini untuk mendeskripsikan perkembangan sekolah Islam di Singkawang pada era kolonialisme Hindia-Belanda (1901-1942). Era ini ditandai dengan terjadinya transformasi pendidikan Islam dari corak tradisional ke formal, yang didorong perlunya pengintegrasian pelajaran umum. Hal ini menjadi menarik bahwa sekolah Islam mampu eksis di tengah pesatnya sekolah Misi Katolik dan dominasi masyarakat Tionghoa di Singkawang. Berdasarkan hasil penelitian melalui metode sejarah dengan tahapan heuristik, verifikasi, interpretasi, dan historiografi, menunjukkan hal berikut. Pendidikan Islam tradisional masih mendominasi pada awal abad ke-20 lewat pengajian dan alim-ulama sebagai pengajarnya. Praktik ini terjadi di beberapa tempat sekitar Singkawang, seperti di masjid besar (jami’), surau di Selakau pimpinan H. Muhammad As’ad, Semelagi, dan kampung-kampung Melayu lainnya. Didorong berkembangnya paham Pan Islamisme, keberadan bumiputera terpelajar, dan ordonansi sekolah liar, pendidikan Islam bercorak tradisional itu bertransformasi menjadi sekolah formal. Sekolah Islam yang pernah berdiri di Singkawang di era ini antara lain Islamiyah School di pusat kota, Madrasah di Semelagi Besar, Semelegi Kecil, Sungai Daun, Setapuk Besar, Madrasah Diniyah Setapuk, dan Ahhadiah School Sedau. Kurikulum yang digunakan tetap menekankan pelajaran agama Islam ditambah pelajaran umum yang ada di Volkschool tiga tahun dan Standaarschool lima tahun. Keberadaan sekolah Islam di kota ini telah mendorong lahirnya pergerakan kebangsaan dengan berdirinya berbagai organisasi pergerakan nasional.